Răspuns :
Răspuns:
Explicație pas cu pas:
[tex]A^{3} = I_{2} \\A^{12} = (A^{3})^{4} = (I_{2})^{4} = I_{2}\\A^{23} = A^{21}*A^{2} = (A^{3})^{7}*A^{2} = (I_{2})^{7}*A^{2} = I_{2}*A^{2}=A^{2}\\A^{34} = A^{33}*A = (A^{3})^{11}*A = (I_{2})^{11}*A = I_{2}*A = A[/tex]
asadar:
[tex]A^{12} + A^{23} + A^{34} = I_{2} + A^{2} +A = A^{2} + A + I_{2} = 0[/tex] (conform cu subpunctul a)
[tex]A^{12} = A^{4 * 3} = {A ^ {3}} ^ 4 = {I_{2}}^4 = I_{2}[/tex]
[tex]A^{23} = A^{3* 7 + 2} = A^{21} * A^{2} = I_{2}^{7} * A^{2} = I_2 * A^{2} = A^{2}[/tex][tex]A^{34} = A^{3* 11 + 1} = A^{33} * A^{1} = I_{2}^{11} * A^{1} = I_2 * A^{1} = A^{1}[/tex]
[tex]A^{12} + A ^ {23} + A ^ {34} = A^{2} + A^{1} + I^{1}\\
[/tex]
Conform pct a)[tex]A^{2} + A^{1} + I^{1} = O_2 => A^{12} + A^{23} + A^{34} = O_2[/tex]